Circular Economy - How Viable is this Model in a Market Economy - Nicoleta SEICARU BUCATA; Liviu MARCUTA (Communications of International Proceedings, 2024)
The circular economy is a very important subject nowadays. Many try to show the advantages of the principle “Reduce, Reuse, and Recycle” of circular economy against the principle “take-make-use-dispose” of the traditional linear economy. But also, some critiques have been raised. We want everything to be circular but in this run we can see that society is not yet prepared. At the same time, producers must be more responsible, even forced by the rules. The products must be designed to be re-used. Recent advances in technology, like AI and Industry 4.0 may help in this direction. Another important issue is the illegal export of waste (especially e-waste) to poor countries. In this article we try to address these issues, starting with available literature research and to find solutions.
Keywords: Traditional Linear Economy; Circular Economy; Critiques of the Circular Economy